ChemInform Abstract: Asymmetric Michael Addition of Cyclohexanone or Cyclopentanone to Chalcones Catalyzed by an L‐Proline‐Based Organic Phosphane. Issue 38 (30th August 2013) - Liu, Lingyan; Zhu, Yunna; Huang, Kaimeng; Chang, Weixing; Li, Jing
Abstract The reaction of cyclohexanone proceeds with excellent dia‐ and enantioselectivities.